Replacing Field Grass by Cassava Leaf Silage Added with Kefir on Productivity of Lactating Dairy Cow - Amir, Azhar; Atabany, Afton; Mubarak, Ade Syahrul; Susanty, Hilda; Syawal, Sutomo (Jurnal Ilmu Ternak Universitas Padjadjaran, 2026)
This study aimed to analyze the effect of cassava leaf silage (CLS) with added kefir on the productivity of lactating dairy cows when replacing field grass. Four Holstein Friesian cows in the early lactation phase (66 ± 11 days in lactation) in the second lactation cycle were randomly divided into four dietary treatments based on a 4×4 Latin square design. Diet treatments consisted of control (50% field grass + 25% concentrate + 25% tofu dregs); CLS 0 Kf (30% field grass + 20% CLS with no added kefir + 25% concentrate + 25% tofu dregs); CLS 2.5 Kf (30% field grass + 20% CLS with 2.5% added kefir + 25% concentrate + 25% tofu dregs); and CLS 5 Kf (30% field grass + 20% CLS with 5% added kefir + 25% concentrate + 25% tofu dregs). Results showed differences between treatments in dry matter intake, crude protein, crude fat, and total digestible nutrients (TDN); milk yield; 4% fat-corrected milk (FCM); and milk fat showed significant differences (P<0.05). In conclusion, CLS supplemented with 5% kefir can replace field grass in ruminant diets for lactating cows by increasing nutrient consumption, milk production, and milk fat without changing milk composition and feed efficiency.